A polyurethane or polyurethane urea material and its preparation method and application
By modifying polyurethane or polyurethane urea materials, the problems of poor durability and anticoagulation requirements of existing heart valve materials are solved, and the mechanical properties and biocompatibility of the materials are improved, which is suitable for the application of polymer heart valves.
Patent Information
- Application Number
- CN202410041617.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-11
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-01-11
AI Technical Summary
The existing artificial heart valves have the disadvantages of lifelong anticoagulation of mechanical valves and poor durability of biological valves, which limit their clinical application.
By using modified polyurethane or polyurethaneurea materials, the material is copolymerized by the mixed large glycol as a flexible chain segment with a curing agent and a chain extender, and crosslinking by crosslinking agent, improving the mechanical properties and biocompatibility of the material.
The modified materials have excellent comprehensive mechanical properties and good biocompatibility. They are suitable for raw materials for implant/interventional medical devices, and are especially preferred for polymer heart valves.
Smart Images

Figure CN117843909B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of medical device materials, and in particular to a modified polyurethane or polyurethane urea material and a preparation method and application thereof. Background Art
[0002] Heart valves refer to valves between the atria and ventricles or between the ventricles and arteries. Valves play a key role in the heart's never-ending blood circulation: valves are like gatekeepers, preventing blood from flowing back into the atria or ventricles that have just left. Artificial heart valves are one of the most commonly used implant materials in the cardiovascular field. Mechanical valves and biological valves have been used for half a century and have become a very important medical device in the field of cardiovascular treatment. Existing artificial heart valves have disadvantages such as the need for lifelong anticoagulation of mechanical valves and poor durability of biological valves, which limits their clinical application. With the extension of life expectancy and the increasing incidence of degenerative valvular heart disease, the demand for artificial heart valves will continue to increase. Therefore, finding more suitable alternatives has always been a research hotspot in the field of heart valves.
[0003] Polymer materials are one of the most widely studied artificial valve materials. Polyurethane (abbreviated as "PU") is one of the fastest growing polymer materials. It is polymerized from diisocyanate and polyol as basic raw materials and has good wear resistance, tear resistance and flexural resistance. However, its water resistance and thermal stability are poor, which limits its application range. Therefore, using polysiloxane to improve the surface properties and biological properties of PU materials is a future development trend.
[0004] Therefore, based on the problems existing in the prior art, it is necessary to develop a material with improved surface properties and biological properties for application in artificial heart valves. Summary of the invention
[0005] In view of this, the present invention provides a modified polyurethane or polyurethane urea material, which is obtained by copolymerizing a mixed macrodiol as a flexible chain segment with a curing agent and a chain extender to obtain a linear polymer, and then cross-linking with a cross-linking agent;
[0006] The flexible segment is composed of a macrodiol composed of a mixture of two diols: a macromolecular alcohol and polydimethylsiloxane;
[0007] The curing agent includes at least one diisocyanate;
[0008] The chain extender includes at least one diol or at least one diamine;
[0009] The crosslinking agent comprises at least one isocyanate having a functionality of not less than 3 or at least one polyol having a functionality of not less than 3;
[0010] The linear polymer has a repeating unit structure of Formula 1:
[0011] ;
[0012] Wherein, A is the diol or diamine, B is the diisocyanate, C is the macromolecular alcohol, and D is the polydimethylsiloxane; n is an integer of 1-100, m is an integer of 1-100, and p is an integer of 1-100.
[0013] Optionally, the macromolecular alcohol is obtained from at least one of poly(hexylene oxide), poly(heptyl oxide), poly(octyl oxide), poly(decyl oxide), polydimethylsiloxane diol, poly(butadiene) diol, poly(carbonate) diol, poly(isobutylene) diol, dimethylsiloxane diol, polyoxyhexamethylene (abbreviated as "PHMO"), polyoctanediol, polydecanediol, polycarbonate diol, and polytetramethylene glycol.
[0014] Optionally, the polydimethylsiloxane includes at least one of α,ωbis(6-hydroxyethoxypropyl)polydimethylsiloxane, α,ωbis(3-aminopropyl)polydimethylsiloxane, α,ωbis(aminomethyl)polydimethylsiloxane, α,ωbis(2-aminoethyl)polydimethylsiloxane, α,ωbis(4-aminobutyl)polydimethylsiloxane, and α,ωbis(5-aminopentyl)polydimethylsiloxane.
[0015] Optionally, the molecular weight of the macroalcohol is 500-1500 Da.
[0016] Optionally, the diisocyanate includes 1,4-diisocyanatobutane, 1,12-diisocyanatododecane, 1,6-diisocyanatehexane, 1,8-diisocyanateoctane, 4,4′-methylenediphenyl diisocyanate, 4,4′-methylenebis(cyclohexyl)diisocyanate, p-phenylene diisocyanate, m-phenylene diisocyanate, trans-cyclohexane-1,4-diisocyanate or a mixture of cis and trans isomers, 1,6-hexamethylene diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, p-tetramethylxylene diisocyanate, isophorone diisocyanate and m-tetramethylxylene diisocyanate, 1,6-diisocyanatohexane, 1,3-bis(1-isocyanato-1-methylethyl)benzene and 1 , at least one of 5-diisocyanatonaphthalene, isophorone diisocyanate (abbreviated as "IPDI"), dicyclohexylmethane-4,4'-diisocyanate (abbreviated as "HMDI"), hexamethylene diisocyanate (abbreviated as "HDI"), toluene 2,4 diisocyanate (abbreviated as "TDI"), and diphenylmethane diisocyanate (abbreviated as "MDI").
[0017] Optionally, the diisocyanate includes at least one of aliphatic isocyanate and aromatic isocyanate polymer; the aliphatic isocyanate includes at least one of HDI and IPDI; and the aromatic isocyanate polymer includes MDI.
[0018] Optionally, the chain extender comprises at least one silicon-containing diol and at least one silicon-free diol.
[0019] Optionally, the silicon-free diol includes at least one of 1,2-ethylene glycol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 1,6-hexanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,4-cyclohexanedimethanol, p-xylene glycol, 1,4-bis(2-hydroxyethoxy)benzene, and 1,12-dodecanediol.
[0020] Optionally, the silicon-containing diol includes tetramethylsiloxane, and the tetramethylsiloxane includes at least one of 1,3-bis(4-hydroxybutyl)-1,1,3,3-tetramethyldisiloxane (abbreviated as "BHTD"), 1,3-bis(3-hydroxypropyl)tetramethyldisiloxane, and 1,3-bis(3-hydroxyisobutyl)tetramethyldisiloxane.
[0021] Optionally, the diamine includes at least one of 1,2-ethylenediamine (abbreviated as "EDA"), ethanolamine, 1,4-butanediamine, 1,3-propylenediamine, and p-phenylenediamine.
[0022] Optionally, the isocyanate with a functionality of not less than 3 includes at least one of an MDI polymer, an HDI polymer (models such as WANNATE® HT-100, CORONATE® HK), an IPDI polymer (models such as Desmodur® Z4470 BA), a TDI polymer (models such as Desmodur® L75), and a pentamethylene diisocyanate (PDI for short) polymer (models such as STABIO® D-3725N).
[0023] Optionally, the polyol having a functionality of not less than 3 includes at least one of glycerol, trimethylolpropane, pentaerythritol, sorbitol, and dipentaerythritol.
[0024] Optionally, the weight ratio of the macrodiol, the curing agent, the chain extender and the crosslinking agent is (48-56): (30-36): (11-16): (0.02-2). By setting this weight ratio, the macrodiol and the curing agent fully react, that is, the functional group hydroxyl group of the macrodiol is fully bonded with the functional group of the curing agent.
[0025] Optionally, the weight ratio of the macromolecular alcohol to the polydimethylsiloxane is 1:4.
[0026] Based on the same inventive concept, the present application also provides a linear polymer for polyurethane or polyurethane urea material, characterized in that the linear polymer has a repeating unit structure of Formula 1:
[0027] ;
[0028] Wherein, A is the diol or diamine, B is the diisocyanate, C is the macromolecular alcohol, and D is the polydimethylsiloxane; n is an integer of 1-100, m is an integer of 1-100, and p is an integer of 1-100.
[0029] Based on the same inventive concept, the present application also provides a method for preparing the above-mentioned modified polyurethane or polyurethane urea material, comprising the following steps:
[0030] The macrodiol and the curing agent are mixed to obtain a prepolymer; the prepolymer is mixed with a chain extender to extend the chain of the prepolymer to obtain a linear polymer; the linear polymer is mixed with a crosslinking agent to react to obtain a polyurethane or polyurethane urea solution; the polyurethane or polyurethane urea solution is coated into a film to obtain the modified polyurethane or polyurethane urea material.
[0031] Based on the same inventive concept, the present application also provides an application of the modified polyurethane or polyurethane urea material, or the modified polyurethane or polyurethane urea material prepared by the above preparation method, as a raw material for implantable / interventional medical devices. The implantable / interventional medical devices may include heart valves, biological implants, and drug delivery devices.
[0032] Compared with the prior art, the technical solution of the embodiment of the present invention has beneficial effects.
[0033] For example, when amines are used as chain extenders, the reaction is violent and a large amount of heat is released, making the reaction temperature difficult to control and prone to side reactions, so the reaction needs to be carried out under low temperature conditions. At the same time, excessive viscosity or gelation is likely to occur during the reaction, which hinders the reaction. The present invention reduces the use of or does not use amines as chain extenders, but increases the use of or uses all mildly reactive alcohols as chain extenders. Specifically, the present invention avoids the use of amines or excessive use of amines to generate high temperatures and avoids the occurrence of gelation during the reaction by ① using at least one diol, ② using a combination of at least one silicon-containing diol and at least one silicon-free diol, or ③ using at least one diol and at least one small amount of diamine, so as to achieve the goal of not requiring low-temperature treatment, that is, the reaction process can be better controlled to prevent the reaction from being blocked, which is beneficial to the batch stability control of the product.
[0034] For another example, the present invention introduces a crosslinking agent, namely, at least one isocyanate with a functionality of not less than 3 or at least one polyol with a functionality of not less than 3, which can effectively increase the crosslinking density and cohesion, reduce the reaction time, and improve the mechanical aging properties of the material, thereby modifying the polyurethane / polyurethane urea.
[0035] For another example, the preparation process of the present invention is simple, and it is easy to design and mass produce. Experimental results show that the material prepared by the present invention has excellent comprehensive mechanical properties and good biocompatibility, and can be better applied to raw materials of implantable / interventional medical devices, especially as the preferred material of polymer heart valves. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 It is the infrared absorption spectrum of the macromolecular alcohol in the embodiment of the present invention.
[0037] Figure 2 It is the infrared absorption spectrum of the modified polyurethane or polyurethane urea material in the embodiment of the present invention.
[0038] Figure 3 It is the cytotoxicity test result of the modified polyurethane or polyurethane urea material in the embodiment of the present invention.
[0039] Figure 4 It is the test result of the hemolysis experiment of the modified polyurethane or polyurethane urea material in the embodiment of the present invention.
[0040] Figure 5 It is a schematic diagram of the cross-linked polymerization structure of the modified polyurethane or polyurethane urea in the embodiment of the present invention. DETAILED DESCRIPTION
[0041] In order to make the purpose, features and beneficial effects of the present invention more obvious and understandable, the specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. It is understood that the specific embodiments described below are only used to explain the present invention, rather than to limit the present invention. In addition, the same or similar reference numerals may be used in the figures to refer to the same or similar elements in different embodiments, and the description of the same or similar elements in different embodiments and the description of the prior art elements, features, effects, etc. may be omitted.
[0042] As shown in this specification and claims, unless otherwise specified or obvious from the context, all numerical values provided herein are modified by the term "about", which should be understood as being within the normal tolerance range in the art. "About" can be understood as allowing a tolerance of 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, 1%, 0.5%, 0.1%, 0.05% or 0.01% of the numerical value.
[0043] The embodiment of the present invention provides a modified polyurethane or polyurethane urea material, wherein the modified polyurethane or polyurethane urea material is obtained by obtaining a linear polymer by a block method from a flexible soft segment and a hard segment, and then crosslinking with a crosslinking agent to obtain a network polymer. Specifically, the flexible soft segment is a macromolecular alcohol and a polydimethylsiloxane diol mixed to form a macrodiol; the hard segment is composed of a curing agent and a chain extender. The flexible segment is sequentially copolymerized with a curing agent and a chain extender to obtain a linear polymer, and then the linear polymer is crosslinked with a crosslinking agent to obtain a polyurethane or polyurethane urea material.
[0044] The curing agent includes at least one diisocyanate;
[0045] The chain extender includes at least one diol or at least one diamine;
[0046] The crosslinking agent includes at least one isocyanate having a functionality of not less than 3 or at least one polyol having a functionality of not less than 3;
[0047] The linear polymer has the structure of Formula 1:
[0048] ;
[0049] Wherein, A is a diol or a diamine, B is a diisocyanate, C is a macromolecular alcohol, and D is a polydimethylsiloxane; n is an integer of 1-100, m is an integer of 1-100, and p is an integer of 1-100.
[0050] Specifically, when A is a diol, A and B form an amide bond, and the linear polymer is a polyurethane polymer. When A is a diamine, A and B form a urea bond, and the linear polymer is a polyurethane urea polymer.
[0051] The above-mentioned repeating unit structure of formula 1 can be further expanded to be expressed as:
[0052] ;
[0053] Wherein, A is a diol or a diamine, B is a diisocyanate, C is a macromolecular alcohol, and D is a polydimethylsiloxane; e is an integer of 1-100, f is an integer of 1-100, and j is an integer of 1-100.
[0054] In some embodiments, the raw material of the macromolecular alcohol is selected from at least one of poly(hexylene oxide), poly(heptyl oxide), poly(octyl oxide), poly(decyl oxide), polydimethylsiloxane diol, poly(butadiene) diol, poly(carbonate) diol, poly(isobutylene) diol, dimethylsiloxane diol, polyoxyhexamethylene (abbreviated as "PHMO"), polyoctanediol, polydecanediol, polycarbonate diol and polytetramethylene glycol, and is obtained by reacting at least one of the above raw materials with a curing agent (such as MDI, IPDI, etc.).
[0055] In some embodiments, the polydimethylsiloxane is selected from at least one of α,ω bis(6-hydroxyethoxypropyl) polydimethylsiloxane, α,ω bis(3-aminopropyl) polydimethylsiloxane, α,ω bis(aminomethyl) polydimethylsiloxane, α,ω bis(2-aminoethyl) polydimethylsiloxane, α,ω bis(4-aminobutyl) polydimethylsiloxane, and α,ω bis(5-aminopentyl) polydimethylsiloxane.
[0056] In some embodiments, the macroalcohol has a molecular weight of 500-1500 Da.
[0057] In some embodiments, the diisocyanate is selected from the group consisting of 1,4-diisocyanatobutane, 1,12-diisocyanatododecane, 1,6-diisocyanatehexane, 1,8-diisocyanateoctane, 4,4′-methylenediphenyl diisocyanate, 4,4′-methylenebis(cyclohexyl)diisocyanate, p-phenylene diisocyanate, m-phenylene diisocyanate, trans-cyclohexane-1,4-diisocyanate or a mixture of cis and trans isomers, 1,6-hexamethylene diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, p-tetramethylxylene diisocyanate, isophorone diisocyanate and m-tetramethylxylene diisocyanate, 1,6-diisocyanatohexane, 1,3-bis(1-isocyanato-1-methylethyl)benzene and 1 , at least one of 5-diisocyanatonaphthalene, isophorone diisocyanate (abbreviated as "IPDI"), dicyclohexylmethane-4,4'-diisocyanate (abbreviated as "HMDI"), hexamethylene diisocyanate (abbreviated as "HDI"), toluene 2,4 diisocyanate (abbreviated as "TDI"), and diphenylmethane diisocyanate (abbreviated as "MDI").
[0058] In a specific embodiment, the diisocyanate is selected from at least one of aliphatic isocyanate and aromatic isocyanate polymer; the aliphatic isocyanate is selected from at least one of HDI and IPDI; and the aromatic isocyanate polymer is MDI.
[0059] In some embodiments, the diol is selected from at least one of 1,2-ethanediol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 1,6-hexanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,4-cyclohexanedimethanol, p-xylene glycol, 1,4-bis(2-hydroxyethoxy)benzene, 1,12-dodecanediol, and tetramethylsiloxane.
[0060] In some embodiments, the tetramethylsiloxane is selected from at least one of 1,3-bis(4-hydroxybutyl)-1,1,3,3-tetramethyldisiloxane (BHTD), 1,3-bis(3-hydroxypropyl)tetramethyldisiloxane, and 1,3-bis(3-hydroxyisobutyl)tetramethyldisiloxane.
[0061] In some embodiments, the diamine is selected from at least one of 1,2-ethylenediamine (EDA), ethanolamine, 1,4-butylenediamine, 1,3-propylenediamine, and p-phenylenediamine.
[0062] In some embodiments, the isocyanate with a functionality of not less than 3 includes MDI polymer, HDI polymer (models such as WANNATE ® HT-100, CORONATE ® HK), IPDI polymer (optional models such as Desmodur ® Z4470 BA), TDI polymer (optional models such as Desmodur ® L75), PDI polymer (optional models such as STABIO ® D-3725N). For example, the HDI polymer with a functionality of 3, i.e., HDI trimer, is obtained by trimerization of HDI under catalysis, and so on.
[0063] In some embodiments, the polyol having a functionality of not less than 3 is selected from at least one of glycerol, trimethylolpropane, pentaerythritol, sorbitol, and dipentaerythritol.
[0064] In some embodiments, the weight ratio of macrodiol, curing agent, chain extender and crosslinking agent is (48-56): (30-36): (11-16): (0.02-2).
[0065] The present invention provides a method for preparing the modified polyurethane or polyurethane urea material, comprising the following steps: mixing a macrodiol and a curing agent to obtain a prepolymer; mixing the prepolymer with a chain extender to extend the chain of the prepolymer to obtain a linear polymer; mixing the linear polymer with a crosslinking agent to obtain a polyurethane or polyurethane urea solution; coating the polyurethane or polyurethane urea solution into a film to obtain the modified polyurethane or polyurethane urea material. Specific embodiments are as follows: Example 1
[0066] Preparation of macroalcohols
[0067] 700 g / mol of polyhexamethylene oxide (abbreviated as "PHMO") was dried under vacuum conditions of 0.1 mbar and 105°C for 15 h. 143.396 mmol of pre-dried PHMO was accurately weighed and placed in a three-necked round-bottom flask equipped with a magnetic stirrer and a nitrogen inlet. The flask was placed in an oil bath at 80°C. 71.698 mmol of molten MDI was placed in the addition funnel and stirred into the flask containing PHMO within 1 minute. After the addition of MDI was completed, the reaction mixture in the flask was further reacted for 2 h to obtain the macromolecular alcohol C: PHMO-MDI-PHMO. The -NCO at 2270 cm in the Fourier transform infrared (abbreviated as "FTIR") spectrum was -1 The disappearance of the absorption peak at 100° was used to confirm the completion of the reaction (see Figure 1 ).
[0068] The macroalcohol C has the structure of formula 2:
[0069] ;
[0070] Here, x is an integer in the range of 1-14, and y is an integer in the range of 1-14.
[0071] MDI has the structure of formula 3:
[0072] .
[0073] Preparation of linear copolymers
[0074] The molten MDI was weighed into a three-necked round-bottom flask equipped with a mechanical stirrer and a nitrogen inlet, and the flask was placed in an oil bath at 70°C. The pre-dried mixture of macroalcohol PHMO-MDI-PHMO and polydimethylsiloxane (i.e., macrodiol soft chain segment) was quickly added to the flask using an addition funnel while stirring. After the addition was complete, the reaction mixture in the flask was heated to 80°C in an oil bath and stirred continuously for 2 h under nitrogen until uniform to obtain a prepolymer.
[0075] Polydimethylsiloxane (PDMS) has the structure of Formula 4:
[0076] ;
[0077] Here, z is an integer in the range of 1-19.
[0078] The prepolymer was first chain extended with BHTD at 80°C and stirred for 2 hours under nitrogen. The solvent anhydrous dimethylacetamide (abbreviated as "anhydrous DMAc") was added to obtain a transparent intermediate prepolymer solution. The diluted EDA solution was dripped dropwise into the cooled reaction solution. The reaction temperature needed to be controlled within 10°C and stirred slowly during the whole process. After EDA was completely added, it was stirred for another 30 minutes. Then the temperature was raised to 80°C, and the diluted 1,2-ethylene glycol solution was added, and stirred for another 4 hours until all the MDI reacted with the chain extender EDA and 1,2-ethylene glycol to obtain a linear copolymer.
[0079] Preparation of cross-linked copolymers
[0080] Heat the linear copolymer to 80°C and continue stirring. Add the multifunctional compound HDI polymer, specifically WANNATE ® HT-100, continue to react for 30 minutes, and obtain a clear solution, namely polyurethane and polyurethane urea (abbreviated as "SiPUU") solution. The cross-linked polymer structure of polyurethane or polyurethane urea can be found in Figure 5 , Figure 5 The middle curve represents a linear polymer, and the sphere represents a cross-linking agent. The linear polymer and the cross-linking agent are mixed and reacted, and the linear polymer is cross-linked through the functional groups of the cross-linking agent to obtain a cross-linked polymer.
[0081] The SiPUU solution was coated into a film. The specific steps are as follows: the SiPUU solution was coated on a coating machine at 50°C, evaporated in a nitrogen oven at 60°C for 24 hours, and then further dried for 24 hours under a vacuum environment of 0.1 mbar. The SiPUU film was peeled off from the culture dish after being soaked in water for about 30 minutes. Finally, it was dried for 24 hours under a vacuum environment of 50°C and 0.1 mbar to remove moisture. Annealing at 125°C for 2 hours gave a modified polyurethane and polyurethane urea elastomer film with a thickness of 0.2mm-0.3mm. The weight ratio of the above raw materials is according to the ratio in Table 1. The modified polyurethane and polyurethane urea were subjected to Fourier transform infrared (abbreviated as "FTIR") spectroscopy to confirm the material structure (see Figure 2 ). Example 2
[0082] Preparation of macroalcohols
[0083] 700 g / mol of PHMO was dried under vacuum conditions of 0.1 mbar and 105°C for 15 h, and 143.396 mmol of pre-dried PHMO was accurately weighed and placed in a three-necked round-bottom flask equipped with a magnetic stirrer and a nitrogen inlet, and the flask was placed in an oil bath at 80°C. 71.698 mmol of molten MDI was placed in the addition funnel and stirred into the flask containing PHMO within 1 minute. After the addition of MDI was completed, the reaction mixture in the flask was further reacted for 2 h to obtain the macromolecular alcohol PHMO-MDI-PHMO. The -NCO at 2270 cm in the Fourier transform infrared (abbreviated as "FTIR") spectrum was -1 The disappearance of the absorption peak at was used to detect the completion of the reaction.
[0084] Preparation of linear copolymers
[0085] The molten MDI was weighed into a three-necked round-bottom flask equipped with a planetary mixer and a nitrogen inlet, and the flask was placed in an oil bath at 70°C. The mixture of the pre-dried macroalcohol PHMO-MDI-PHMO and polydimethylsiloxane was quickly added to the flask with a feeding funnel while stirring. After the addition was complete, the reaction mixture in the flask was heated to 80°C in an oil bath and stirred continuously for 2 h under nitrogen until uniform to obtain a prepolymer.
[0086] The prepolymer was first chain extended with BHTD at 80°C and stirred for 2 hours under nitrogen. Anhydrous dimethylacetamide (abbreviated as "anhydrous DMAc") was added to obtain a transparent intermediate prepolymer solution. The diluted EDA solution was dripped dropwise into the cooled reaction solution. The reaction temperature needed to be controlled within 10°C during the whole process and stirred slowly. After EDA was completely added, it was stirred for another 30 minutes. Then the temperature was raised to 80°C, and the diluted 1,2-butanediol solution was added, and stirred for another 4 hours until all MDI reacted with the chain extender EDA and 1,2-butanediol to obtain a linear copolymer.
[0087] Preparation of cross-linked copolymers
[0088] Heat the linear copolymer to 80°C and continue stirring. Add the multifunctional compound HDI polymer, specifically WANNATE ® HT-100, continue to react for 30 minutes to obtain a clear solution, namely, polyurethane and polyurethane urea (abbreviated as "SiPUU") solution.
[0089] The SiPUU solution is coated into a film. The specific steps are: coat the SiPUU solution on a coating machine at 50°C, evaporate it in a nitrogen oven at 60°C for 24 hours, and then further dry it for 24 hours under a vacuum environment of 0.1mbar. The SiPUU film is soaked in water for about 30 minutes and peeled off from the culture dish. Finally, it is dried at 50°C and 0.1mbar in a vacuum environment for 24 hours to remove moisture. Annealing at 125°C for 2 hours will obtain a modified polyurethane and polyurethane urea elastomer film with a thickness of 0.2mm-0.3mm. The weight ratio of the above raw materials is according to the ratio in Table 1. Example 3
[0090] Preparation of macroalcohols
[0091] 700 g / mol of PHMO was dried under vacuum conditions of 0.1 mbar and 105°C for 15 h, and 143.396 mmol of pre-dried PHMO was accurately weighed and placed in a three-necked round-bottom flask equipped with a magnetic stirrer and a nitrogen inlet, and the flask was placed in an oil bath at 80°C. 71.698 mmol of molten MDI was placed in the addition funnel and stirred into the flask containing PHMO within 1 minute. After the addition of MDI was completed, the reaction mixture in the flask was further reacted for 2 h to obtain the macromolecular alcohol PHMO-MDI-PHMO. The -NCO at 2270 cm in the Fourier transform infrared (abbreviated as "FTIR") spectrum was -1 The disappearance of the absorption peak at was used to detect the completion of the reaction.
[0092] Preparation of linear copolymers
[0093] The molten MDI was weighed into a three-necked round-bottom flask equipped with a planetary mixer and a nitrogen inlet, and the flask was placed in an oil bath at 70°C. The mixture of the pre-dried macroalcohol PHMO-MDI-PHMO and polydimethylsiloxane was quickly added to the flask with a feeding funnel while stirring. After the addition was complete, the reaction mixture in the flask was heated to 80°C in an oil bath and stirred continuously for 2 h under nitrogen until uniform to obtain a prepolymer.
[0094] The prepolymer is first chain extended with BHTD at 80°C and stirred under nitrogen for 2 hours. Anhydrous dimethylacetamide (abbreviated as "anhydrous DMAc") is added to obtain a transparent intermediate prepolymer solution. The diluted solution of p-phenylenediamine is dripped dropwise into the cooled reaction solution. The reaction temperature needs to be controlled within 10°C and stirred slowly during the whole process. After the p-phenylenediamine is completely added, stir for another 30 minutes. Then raise the temperature to 80°C, add the diluted solution of 1,3-butanediol, and stir for another 4 hours until all MDI reacts with the chain extenders p-phenylenediamine and 1,3-butanediol to obtain a linear copolymer.
[0095] Preparation of cross-linked copolymers
[0096] Heat the linear copolymer to 80°C and continue stirring. Add the multifunctional compound HDI polymer, specifically WANNATE ® HT-100, continue to react for 30 minutes to obtain a clear solution, namely, polyurethane and polyurethane urea (abbreviated as "SiPUU") solution.
[0097] The SiPUU solution is coated into a film. The specific steps are: coat the SiPUU solution on a coating machine at 50°C, evaporate it in a nitrogen oven at 60°C for 24 hours, and then further dry it for 24 hours under a vacuum environment of 0.1mbar. The SiPUU film is soaked in water for about 30 minutes and peeled off from the culture dish. Finally, it is dried at 50°C and 0.1mbar in a vacuum environment for 24 hours to remove moisture. Annealing at 125°C for 2 hours will obtain a modified polyurethane and polyurethane urea elastomer film with a thickness of 0.2mm-0.3mm. The weight ratio of the above raw materials is according to the ratio in Table 1. Example 4
[0098] Preparation of macroalcohols
[0099] 700 g / mol of PHMO was dried under vacuum conditions of 0.1 mbar and 105°C for 15 h, and 143.396 mmol of pre-dried PHMO was accurately weighed and placed in a three-necked round-bottom flask equipped with a magnetic stirrer and a nitrogen inlet, and the flask was placed in an oil bath at 80°C. 71.698 mmol of molten MDI was placed in the addition funnel and stirred into the flask containing PHMO within 1 minute. After the addition of MDI was completed, the reaction mixture in the flask was further reacted for 2 h to obtain the macromolecular alcohol PHMO-MDI-PHMO. The -NCO at 2270 cm in the Fourier transform infrared (abbreviated as "FTIR") spectrum was -1 The disappearance of the absorption peak at was used to detect the completion of the reaction.
[0100] Preparation of linear copolymers
[0101] The molten MDI was weighed into a three-necked round-bottom flask equipped with a mechanical stirrer and a nitrogen inlet, and the flask was placed in an oil bath at 70°C. The mixture of the pre-dried macroalcohol PHMO-MDI-PHMO and polydimethylsiloxane was quickly added to the flask with a feeding funnel while stirring. After the addition was complete, the reaction mixture in the flask was heated to 80°C in an oil bath and stirred continuously for 2 h under nitrogen until uniform to obtain a prepolymer.
[0102] The prepolymer was first chain extended with BHTD at 80°C and stirred for 2 hours under nitrogen. Anhydrous dimethylacetamide (abbreviated as "anhydrous DMAc") was added to obtain a transparent intermediate prepolymer solution. The diluted solution of 1,3-propylenediamine was dripped dropwise into the cooled reaction solution. The reaction temperature needed to be controlled within 10°C and stirred slowly during the whole process. After 1,3-propylenediamine was completely added, it was stirred for another 30 minutes. Then the temperature was raised to 80°C, and the diluted solution of 1,10-decanediol 1,4-cyclohexanedimethanol was added, and stirred for another 4 hours until all MDI reacted with the chain extender 1,3-propylenediamine and 1,10-decanediol 1,4-cyclohexanedimethanol to obtain a linear copolymer.
[0103] Preparation of cross-linked copolymers
[0104] The linear copolymer was heated to 80°C and stirred continuously. The multifunctional compound glycerol polymer was added and the reaction was continued for 30 minutes to obtain a clear solution, namely a polyurethane and polyurethane urea (abbreviated as "SiPUU") solution.
[0105] The SiPUU solution is coated into a film. The specific steps are: coat the SiPUU solution on a coating machine at 50°C, evaporate it in a nitrogen oven at 60°C for 24 hours, and then further dry it for 24 hours under a vacuum environment of 0.1mbar. The SiPUU film is soaked in water for about 30 minutes and peeled off from the culture dish. Finally, it is dried at 50°C and 0.1mbar in a vacuum environment for 24 hours to remove moisture. Annealing at 125°C for 2 hours will obtain a modified polyurethane and polyurethane urea elastomer film with a thickness of 0.2mm-0.3mm. The weight ratio of the above raw materials is according to the ratio in Table 1. Example 5
[0106] Preparation of macroalcohol soft segments
[0107] 691.3 g / mol of PHMO was dried under vacuum conditions of 0.1 mbar and 105°C for 15 h. 29.654 mmol of pre-dried PHMO was accurately weighed and placed in a three-necked round-bottom flask equipped with a magnetic stirrer and a nitrogen inlet. The flask was placed in an oil bath at 80°C. 19.494 mmol of IPDI was placed in the addition funnel and stirred and added to the flask containing PHMO within 1 minute. After the addition of IPDI was completed, the reaction mixture in the flask was further reacted for 2 h to obtain the macromolecular alcohol PHMO-IPDI-PHMO. The -NCO at 2270 cm in the Fourier transform infrared (abbreviated as "FTIR") spectrum was determined. -1 The disappearance of the absorption peak at was used to detect the completion of the reaction.
[0108] Preparation of linear copolymers
[0109] The molten IPDI was weighed into a three-necked round-bottom flask equipped with a mechanical stirrer and a nitrogen inlet, and the flask was placed in an oil bath at 70°C. The mixture of the pre-dried macroalcohol PHMO-IPDI-PHMO and polydimethylsiloxane was quickly added to the flask with a feeding funnel while stirring. After the addition was complete, the reaction mixture in the flask was heated to 80°C in an oil bath and stirred continuously for 2 h under nitrogen until uniform to obtain a prepolymer.
[0110] The prepolymer was first chain extended with BHTD at 80°C and stirred for 2 hours under nitrogen. Anhydrous dimethylacetamide (abbreviated as "anhydrous DMAc") was added to obtain a transparent intermediate prepolymer solution. The diluted solution of 1,3-propylenediamine was dripped dropwise into the cooled reaction solution. The reaction temperature should be controlled within 10°C during the whole process and stirred slowly. After 1,3-propylenediamine was completely added, it was stirred for another 30 minutes. Then the temperature was raised to 80°C, and the diluted solution of p-xylene glycol was added, and stirred for another 4 hours until all IPDI reacted with the chain extender 1,3-propylenediamine and p-xylene glycol to obtain a linear copolymer.
[0111] Preparation of cross-linked copolymers
[0112] The linear copolymer was heated to 80°C and stirred continuously. The multifunctional compound glycerol polymer was added and the reaction was continued for 30 minutes to obtain a clear solution, namely a polyurethane and polyurethane urea (abbreviated as "SiPUU") solution.
[0113] The SiPUU solution is coated into a film. The specific steps are: coat the SiPUU solution on a coating machine at 50°C, evaporate it in a nitrogen oven at 60°C for 24 hours, and then further dry it for 24 hours under a vacuum environment of 0.1mbar. The SiPUU film is soaked in water for about 30 minutes and peeled off from the culture dish. Finally, it is dried at 50°C and 0.1mbar in a vacuum environment for 24 hours to remove moisture. Annealing at 125°C for 2 hours will obtain a modified polyurethane and polyurethane urea elastomer film with a thickness of 0.2mm-0.3mm. The weight ratio of the above raw materials is according to the ratio in Table 1. Example 6
[0114] Preparation of macroalcohols
[0115] 700 g / mol of PHMO was dried under vacuum conditions of 0.1 mbar and 105°C for 15 h, 46.245 mmol of pre-dried PHMO was accurately weighed and placed in a three-necked round-bottom flask equipped with a magnetic stirrer and a nitrogen inlet, and the flask was placed in an oil bath at 80°C. 18.4 mmol of molten MDI was placed in the addition funnel and stirred and added to the flask containing PHMO within 1 minute. After the addition of MDI was completed, the reaction mixture in the flask was further reacted for 2 h to obtain the macromolecular alcohol PHMO-MDI-PHMO. The -NCO at 2270 cm in the Fourier transform infrared (abbreviated as "FTIR") spectrum was -1 The disappearance of the absorption peak at was used to detect the completion of the reaction.
[0116] Preparation of linear copolymers
[0117] The molten MDI was weighed into a three-necked round-bottom flask equipped with a planetary mixer and a nitrogen inlet, and the flask was placed in an oil bath at 70°C. The mixture of the pre-dried macroalcohol PHMO-MDI-PHMO and polydimethylsiloxane was quickly added to the flask with a feeding funnel while stirring. After the addition was complete, the reaction mixture in the flask was heated to 80°C in an oil bath and stirred continuously for 2 h under nitrogen until uniform to obtain a prepolymer.
[0118] The prepolymer was first chain extended with BHTD at 80°C and stirred for 2 hours under nitrogen. Anhydrous dimethylacetamide (abbreviated as "anhydrous DMAc") was added to obtain a transparent intermediate prepolymer solution. The diluted solution of 1,4-butanediamine was dripped dropwise into the cooled reaction solution. The reaction temperature needed to be controlled within 10°C and stirred slowly during the whole process. After 1,4-butanediamine was completely added, it was stirred for another 30 minutes. Then the temperature was raised to 80°C, and the diluted solution of 1,4-bis(2-hydroxyethoxy)benzene was added, and stirred for another 4 hours until all MDI reacted with the chain extender 1,4-butanediamine and 1,4-bis(2-hydroxyethoxy)benzene to obtain a linear copolymer.
[0119] Preparation of cross-linked copolymers
[0120] Heat the linear copolymer to 80°C and continue stirring. Add the multifunctional compound HDI polymer, specifically CORONATE ® HK, continue the reaction for 30 minutes to obtain a clear solution, namely, a polyurethane and polyurethane urea (abbreviated as "SiPUU") solution.
[0121] The SiPUU solution is coated into a film. The specific steps are: coat the SiPUU solution on a coating machine at 50°C, evaporate it in a nitrogen oven at 60°C for 24 hours, and then further dry it for 24 hours under a vacuum environment of 0.1mbar. The SiPUU film is soaked in water for about 30 minutes and peeled off from the culture dish. Finally, it is dried at 50°C and 0.1mbar in a vacuum environment for 24 hours to remove moisture. Annealing at 125°C for 2 hours will obtain a modified polyurethane and polyurethane urea elastomer film with a thickness of 0.2mm-0.3mm. The weight ratio of the above raw materials is according to the ratio in Table 1. Example 7
[0122] Preparation of macroalcohols
[0123] 700 g / mol of PHMO was dried under vacuum conditions of 0.1 mbar and 105°C for 15 h, 46.245 mmol of pre-dried PHMO was accurately weighed and placed in a three-necked round-bottom flask equipped with a magnetic stirrer and a nitrogen inlet, and the flask was placed in an oil bath at 80°C. 18.4 mmol of molten MDI was placed in the addition funnel and stirred and added to the flask containing PHMO within 1 minute. After the addition of MDI was completed, the reaction mixture in the flask was further reacted for 2 h to obtain the macromolecular alcohol PHMO-MDI-PHMO. The -NCO at 2270 cm in the Fourier transform infrared (abbreviated as "FTIR") spectrum was -1 The disappearance of the absorption peak at was used to detect the completion of the reaction.
[0124] Preparation of linear copolymers
[0125] The molten MDI was weighed into a three-necked round-bottom flask equipped with a planetary mixer and a nitrogen inlet, and the flask was placed in an oil bath at 70°C. The mixture of the pre-dried macroalcohol PHMO-MDI-PHMO and polydimethylsiloxane was quickly added to the flask with a feeding funnel while stirring. After the addition was complete, the reaction mixture in the flask was heated to 80°C in an oil bath and stirred continuously for 2 h under nitrogen until uniform to obtain a prepolymer.
[0126] The prepolymer was first chain extended with BHTD, and the chain extension temperature was maintained at 80°C under nitrogen for 2 hours under stirring. Anhydrous dimethylacetamide (abbreviated as "anhydrous DMAc") was added to obtain a transparent intermediate prepolymer solution. The diluted solution of 1,2-ethylene glycol was dripped into the cooled reaction solution at 80°C and stirred slowly. After the 1,2-ethylene glycol was completely added, it was stirred for another 4 hours until all the MDI and the chain extender 1,2-ethylene glycol reacted completely to obtain a linear copolymer.
[0127] Preparation of cross-linked copolymers
[0128] Heat the linear copolymer to 80°C and continue stirring. Add the multifunctional compound HDI polymer, specifically CORONATE ® HK, and continue the reaction for 30 minutes to obtain a clear solution, namely, a polyurethane (abbreviated as "SiPUU") solution.
[0129] The SiPUU solution was coated into a film. The specific steps are as follows: the SiPUU solution was coated on a coating machine at 50°C, evaporated in a nitrogen oven at 60°C for 24 hours, and then further dried for 24 hours under a vacuum environment of 0.1mbar. The SiPUU film was soaked in water for about 30 minutes and peeled off from the culture dish. Finally, it was dried at 50°C and 0.1mbar in a vacuum environment for 24 hours to remove moisture. Annealing at 125°C for 2 hours gave a modified polyurethane elastomer film with a thickness of 0.2mm-0.3mm. The weight ratio of the above raw materials is in accordance with the ratio in Table 1. Example 8
[0130] Preparation of macroalcohols
[0131] 700 g / mol of PHMO was dried under vacuum conditions of 0.1 mbar and 105°C for 15 h, 46.245 mmol of pre-dried PHMO was accurately weighed and placed in a three-necked round-bottom flask equipped with a magnetic stirrer and a nitrogen inlet, and the flask was placed in an oil bath at 80°C. 18.4 mmol of molten MDI was placed in the addition funnel and stirred and added to the flask containing PHMO within 1 minute. After the addition of MDI was completed, the reaction mixture in the flask was further reacted for 2 h to obtain the macromolecular alcohol PHMO-MDI-PHMO. The -NCO at 2270 cm in the Fourier transform infrared (abbreviated as "FTIR") spectrum was -1 The disappearance of the absorption peak at was used to detect the completion of the reaction.
[0132] Preparation of linear copolymers
[0133] The molten MDI was weighed into a three-necked round-bottom flask equipped with a planetary mixer and a nitrogen inlet, and the flask was placed in an oil bath at 70°C. The mixture of the pre-dried macroalcohol PHMO-MDI-PHMO and polydimethylsiloxane was quickly added to the flask with a feeding funnel while stirring. After the addition was complete, the reaction mixture in the flask was heated to 80°C in an oil bath and stirred continuously for 2 h under nitrogen until uniform to obtain a prepolymer.
[0134] Add anhydrous dimethylacetamide (abbreviated as "anhydrous DMAc") to the prepolymer to obtain a transparent intermediate prepolymer solution. At 0°C, drop the diluted EDA solution into the cooled reaction solution and stir slowly. The reaction temperature needs to be controlled within 10°C during the whole process and stir slowly. After EDA is completely added, stir for another 30 minutes until all MDI and the chain extender EDA react completely to obtain a linear copolymer.
[0135] Preparation of cross-linked copolymers
[0136] Heat the linear copolymer to 80°C and continue stirring. Add the multifunctional compound HDI polymer, specifically CORONATE ® HK, and continue the reaction for 30 minutes to obtain a clear solution, namely, polyurethane urea (abbreviated as "SiPUU") solution.
[0137] The SiPUU solution is coated into a film. The specific steps are: coat the SiPUU solution on a coating machine at 50°C, evaporate it in a nitrogen oven at 60°C for 24 hours, and then further dry it for 24 hours under a vacuum environment of 0.1mbar. The SiPUU film is soaked in water for about 30 minutes and peeled off from the culture dish. Finally, it is dried at 50°C and 0.1mbar in a vacuum environment for 24 hours to remove moisture. Annealing at 125°C for 2 hours will obtain a modified polyurethane urea elastomer film with a thickness of 0.2mm-0.3mm. The weight ratio of the above raw materials is according to the ratio in Table 1. Example 9
[0138] Preparation of macroalcohols
[0139] 700 g / mol of PHMO was dried under vacuum conditions of 0.1 mbar and 105°C for 15 h, 46.245 mmol of pre-dried PHMO was accurately weighed and placed in a three-necked round-bottom flask equipped with a magnetic stirrer and a nitrogen inlet, and the flask was placed in an oil bath at 80°C. 18.4 mmol of molten MDI was placed in the addition funnel and stirred and added to the flask containing PHMO within 1 minute. After the addition of MDI was completed, the reaction mixture in the flask was further reacted for 2 h to obtain the macromolecular alcohol PHMO-MDI-PHMO. The -NCO at 2270 cm in the Fourier transform infrared (abbreviated as "FTIR") spectrum was -1 The disappearance of the absorption peak at was used to detect the completion of the reaction.
[0140] Preparation of linear copolymers
[0141] The molten MDI was weighed into a three-necked round-bottom flask equipped with a planetary mixer and a nitrogen inlet, and the flask was placed in an oil bath at 70°C. The mixture of the pre-dried macroalcohol PHMO-MDI-PHMO and polydimethylsiloxane was quickly added to the flask with a feeding funnel while stirring. After the addition was complete, the reaction mixture in the flask was heated to 80°C in an oil bath and stirred continuously for 2 h under nitrogen until uniform to obtain a prepolymer.
[0142] Anhydrous dimethylacetamide (DMAc) is added to the prepolymer to obtain a transparent intermediate prepolymer solution. The diluted 1,2-ethylene glycol solution is dripped into the cooled reaction solution at 80°C and stirred slowly. After the 1,2-ethylene glycol is completely added, stir for another 4 hours until all the MDI reacts with the chain extender 1,2-ethylene glycol to obtain a linear copolymer.
[0143] Preparation of cross-linked copolymers
[0144] Heat the linear copolymer to 80°C and continue stirring. Add the multifunctional compound HDI polymer, specifically CORONATE® HK, and continue the reaction for 30 minutes to obtain a clear solution, namely a polyurethane (abbreviated as "SiPUU") solution.
[0145] The SiPUU solution was coated into a film. The specific steps are as follows: the SiPUU solution was coated on a coating machine at 50°C, evaporated in a nitrogen oven at 60°C for 24 hours, and then further dried for 24 hours under a vacuum environment of 0.1mbar. The SiPUU film was soaked in water for about 30 minutes and peeled off from the culture dish. Finally, it was dried at 50°C and 0.1mbar in a vacuum environment for 24 hours to remove moisture. Annealing at 125°C for 2 hours gave a modified polyurethane elastomer film with a thickness of 0.2mm-0.3mm. The weight ratio of the above raw materials is in accordance with the ratio in Table 1.
[0146] Comparative Example 1
[0147] Preparation of macroalcohols
[0148] 700 g / mol of PHMO was dried under vacuum conditions of 0.1 mbar and 105°C for 15 h, and 143.396 mmol of pre-dried PHMO was accurately weighed and placed in a three-necked round-bottom flask equipped with a magnetic stirrer and a nitrogen inlet, and the flask was placed in an oil bath at 80°C. 71.698 mmol of molten MDI was placed in the addition funnel and stirred into the flask containing PHMO within 1 minute. After the addition of MDI was completed, the reaction mixture in the flask was further reacted for 2 h to obtain the macromolecular alcohol PHMO-MDI-PHMO. The -NCO at 2270 cm in the Fourier transform infrared (abbreviated as "FTIR") spectrum was-1 The disappearance of the absorption peak at was used to detect the completion of the reaction.
[0149] Preparation of linear copolymers
[0150] The molten MDI was weighed into a three-necked round-bottom flask equipped with a mechanical stirrer and a nitrogen inlet, and the flask was placed in an oil bath at 70°C. The mixture of the pre-dried macroalcohol PHMO-MDI-PHMO and polydimethylsiloxane was quickly added to the flask with a feeding funnel while stirring. After the addition was complete, the reaction mixture in the flask was heated to 80°C in an oil bath and stirred continuously for 2 h under nitrogen until uniform to obtain a prepolymer.
[0151] The prepolymer was first chain extended with BHTD at 80°C and stirred for 2 hours under nitrogen. Anhydrous dimethylacetamide (abbreviated as "anhydrous DMAc") was added to obtain a transparent intermediate prepolymer solution. The diluted EDA solution was dripped into the cooled reaction solution drop by drop. The reaction temperature should be controlled within 10°C during the whole process and stirred slowly. After EDA was completely added, it was stirred for another 30 minutes until all MDI and the chain extender EDA reacted completely to obtain a linear copolymer.
[0152] The linear copolymer was heated to 80°C and stirred for 30 minutes to obtain a solution.
[0153] The solution is coated into a film. The specific steps are: coat the solution on a coating machine at 50°C, evaporate in a nitrogen oven at 60°C for 24 hours, then further dry under a vacuum environment of 0.1mbar, and soak at the same temperature for another 24 hours. The film is soaked in water for about 30 minutes and peeled off from the culture dish. Finally, it is dried at 50°C and 0.1mbar in a vacuum environment for 24 hours to remove moisture. Annealing at 125°C for 2 hours will obtain a film with a thickness of 0.2mm-0.3mm. The weight ratio of the above raw materials is according to the ratio in Table 1.
[0154] Table 1:
[0155]
[0156] Test experiment:
[0157] The film materials prepared according to the methods shown in the above examples 1-6 and comparative example 1 were subjected to tensile property test according to GBT1040.3-2006. The Shore hardness was tested with a Shore hardness tester. The in vitro cytotoxicity test was conducted according to the method shown in GB / T16886.5-2017. The in vitro hemolytic performance test was conducted according to the method shown in GB / T 16886.4-2022. The test results are shown in Table 2.
[0158] Table 2:
[0159]
[0160] Note: ○ represents the test passed, no toxicity or hemolysis.
[0161] It is not difficult to find from the above experimental data:
[0162] On the one hand, the polyurethane or polyurethane urea material prepared by the preparation method provided by the embodiment of the present invention is compared with the material prepared by the preparation method of the cross-linking chain extender without adding a cross-linking agent (Comparative Example 1). After being subjected to high temperature and high humidity (for example, boiling in water at 95-100°C for 1000 hours as shown in GB / T 41168-2021), its mechanical properties (such as tensile strength and elongation at break after wet treatment) are significantly improved, and both tensile strength and elongation have better retention rates. At the same time, by selecting the appropriate addition amount of each component, its main mechanical performance indicators can also be kept at the same level or improved, such as the various mechanical performance indicators of Example 2: tensile strength after wet treatment, tensile strength retention rate, elongation at break after wet treatment, and elongation retention rate are optimal.
[0163] On the other hand, when amines are used as chain extenders, the reaction speed of amines and isocyanates is fast and violent, and the reaction produces high temperatures and is prone to side reactions. Therefore, the reaction temperature needs to be controlled to keep it at a low temperature. At the same time, excessive viscosity or gelation is likely to occur during the reaction, resulting in uneven reactions. In order to avoid the gelation phenomenon from hindering the normal and stable progress of the reaction and not affecting the processing process, the use of components with mild reactions and not easy to produce gelation as chain extenders can better ensure the normal and stable progress of the reaction. The present invention reduces the use of amines (Examples 1-6) as chain extenders, but increases the use of alcohols as chain extenders to make the reaction process milder, reduce the difficulty of temperature control, and reduce the use of amines. The probability of gelation is also reduced. The present invention does not use amines (Example 7) as chain extenders, but uses all alcohols as chain extenders, so that the chain extender is replaced by alcohols from amines, and there is no risk of high temperature generated by the reaction, so that no low temperature control is required, and alcohols as chain extenders also have no obvious gelation phenomenon, so it can be carried out at high temperatures, and the reaction process can be better controlled, which is beneficial to the batch stability control of the product and provides product uniformity. The present invention further uses a combination of silanol-containing and silanol-free as a chain extender. By adding silanol-containing, reaction compatibility is further provided, and its mechanical properties (such as tensile strength and elongation at break after wet treatment, etc.) are further improved, and both tensile strength and elongation have better retention rates. For example, the various mechanical performance indicators of Example 7 compared to Example 9: tensile strength after wet treatment, tensile strength retention rate, elongation at break after wet treatment, and elongation retention rate are better.
[0164] On the other hand, see Figure 3 As shown, the extract of the polyurethane or polyurethane urea material provided in the embodiment of the present invention is used to carry out biological reaction on L929 mammalian fibroblasts, thereby obtaining the following Figure 3 The cytotoxicity test results shown in FIG. 1 are shown in FIG. 1 , where the lower the cell viability % (i.e., number of live cells / total number of cells), the greater the potential cytotoxicity, and the cell viability % of 100% sample extract is the final test result. The blank control is MEM culture medium containing 10% fetal bovine serum, the positive control is zinc diethyldithiocarbamate, the negative control is high-density polyethylene, and the sample is the SiPUU solution of Example 2. Figure 3 It can be seen that the cell viability value of the 100% extract of the polyurethane or polyurethane urea material provided in the embodiment of the present invention is 90.4%, and has no potential toxic effect on L929 cells.
[0165] On the other hand, see Figure 4 As shown, an in vitro test was performed to evaluate whether the polyurethane or polyurethane urea material provided in the embodiment of the present invention has any adverse effect on hemolytic performance. The sample is the SiPUU solution of Example 2, the negative control is high-density polyethylene, the positive control is nitrile rubber, and the blank control sample is PBS (Phosphate-Buffered Saline). Evaluation criteria: The average blank-corrected hemolytic index is 0-2, which is classified as no hemolysis. The average blank-corrected hemolytic index is 2-5, which is classified as mild hemolysis. The average blank-corrected hemolytic index is >5, which is classified as hemolysis. Figure 4 It can be seen that the blank-corrected hemolysis index of the polyurethane or polyurethane urea material directly contacted with the embodiment of the present invention is 0.16. Therefore, the polyurethane or polyurethane urea material provided by the embodiment of the present invention has no effect on the hemolysis performance.
[0166] In addition, the improved polyurethane or polyurethane urea material provided by the embodiment of the present invention still has excellent biocompatibility, and therefore can be used as a raw material for implantable / interventional medical devices. Implantable / interventional medical devices may include heart valves, biological implants, and drug delivery devices. The preparation method provided by the embodiment of the present invention is also simpler and easier to control.
[0167] Although specific embodiments have been described above, these embodiments are not intended to limit the scope of the present disclosure, even when only a single embodiment is described with respect to specific features. The feature examples provided in the present disclosure are intended to be illustrative rather than limiting, unless otherwise stated. In specific implementations, the technical features of one or more dependent claims may be combined with the technical features of the independent claims, based on actual needs and where technically feasible, and the technical features from the corresponding independent claims may be combined in any appropriate manner rather than just by the specific combinations listed in the claims.
[0168] Although the present invention is disclosed as above, the present invention is not limited thereto. Any person skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the scope defined by the claims.
Claims
1. A polyurethane or polyurethane urea material, characterized in that: A linear polymer obtained by copolymerizing the flexible chain segment with a curing agent and a chain extender in sequence, and then crosslinking with a crosslinking agent; The flexible segment is composed of a macrodiol mixed with a macromolecular alcohol and polydimethylsiloxane; Wherein, the weight ratio of the macromolecular alcohol to the polydimethylsiloxane is 1:4; the weight ratio of the macrodiol, the curing agent, the chain extender and the cross-linking agent is (48-56): (30-36):(11-16):(0.02-2); The raw material of the macromolecular alcohol is selected from at least one of poly(hexylene oxide), poly(heptylene oxide), poly(octylene oxide), poly(decylene oxide), polydimethylsiloxane diol, poly(butadiene) diol, poly(carbonate) diol, poly(isobutylene) diol, dimethylsiloxane diol, polyoxyhexamethylene, polyoctanediol, polydecanediol and polytetrahydrofuran diol, and is obtained by reacting at least one of the above raw materials with a curing agent; The curing agent includes at least one diisocyanate; The chain extender includes at least one silicon-containing diol and at least one silicon-free diol; The cross-linking agent comprises at least one isocyanate having a functionality of not less than 3; The linear polymer has a repeating unit structure of Formula 1: Wherein, A is at least one silicon-containing diol and at least one silicon-free diol, B is the diisocyanate, C is the macromolecular alcohol, and D is the polydimethylsiloxane; n is an integer of 1-100, m is an integer of 1-100, and p is an integer of 1-100.
2. The polyurethane or polyurethane urea material according to claim 1, characterized in that The polydimethylsiloxane includes at least one of α,ω bis(6-hydroxyethoxypropyl) polydimethylsiloxane, α,ω bis(3-aminopropyl) polydimethylsiloxane, α,ω bis(aminomethyl) polydimethylsiloxane, α,ω bis(2-aminoethyl) polydimethylsiloxane, α,ω bis(4-aminobutyl) polydimethylsiloxane, and α,ω bis(5-aminopentyl) polydimethylsiloxane.
3. The polyurethane or polyurethane urea material according to claim 1, characterized in that The molecular weight of the macromolecular alcohol is 500-1500 Da.
4. The polyurethane or polyurethane urea material according to claim 1, characterized in that The diisocyanate includes 1,4-diisocyanatobutane, 1,12-diisocyanatododecane, 1,6-diisocyanatehexane, 1,8-diisocyanateoctane, 4,4′-methylenediphenyl diisocyanate, 4,4′-methylenebis(cyclohexyl)diisocyanate, p-phenylene diisocyanate, m-phenylene diisocyanate, trans-cyclohexane-1,4-diisocyanate or a mixture of cis and trans isomers, 1, At least one of 6-hexamethylene diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, p-tetramethylxylene diisocyanate, isophorone diisocyanate and m-tetramethylxylene diisocyanate, 1,6-diisocyanatohexane, 1,3-bis(1-isocyanato-1-methylethyl)benzene and 1,5-diisocyanatonaphthalene, IPDI, HMDI, HDI, TDI and MDI.
5. The polyurethane or polyurethane urea material according to claim 4, characterized in that The diisocyanate includes at least one of aliphatic isocyanate and aromatic isocyanate polymer; the aliphatic isocyanate includes at least one of HDI and IPDI; the aromatic isocyanate polymer includes MDI.
6. The polyurethane or polyurethane urea material according to claim 1, characterized in that The silicon-free diol includes at least one of 1,2-ethylene glycol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 1,6-hexanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,4-cyclohexanedimethanol, p-xylene glycol, 1,4-bis(2-hydroxyethoxy)benzene, and 1,12-dodecanediol; the silicon-containing diol includes tetramethylsiloxane; the tetramethylsiloxane includes at least one of 1,3-bis(4-hydroxybutyl)-1,1,3,3-tetramethyldisiloxane, 1,3-bis(3-hydroxypropyl)tetramethyldisiloxane, and 1,3-bis(3-hydroxyisobutyl)tetramethyldisiloxane.
7. The polyurethane or polyurethane urea material according to claim 1, characterized in that: The isocyanate with a functionality of not less than 3 includes at least one of an MDI polymer, an HDI polymer, an IPDI polymer, a TDI polymer, and a PDI polymer.
8. The method for preparing the polyurethane or polyurethane urea material according to any one of claims 1 to 7, characterized in that: The following steps are involved: The macrodiol and the curing agent are mixed to obtain a prepolymer; the prepolymer is mixed with a chain extender to extend the chain of the prepolymer to obtain a linear polymer; the linear polymer is mixed with a cross-linking agent to react to obtain a polyurethane or polyurethane urea solution; the polyurethane or polyurethane urea solution is coated into a film to obtain the polyurethane or polyurethane urea material.
9. Use of the polyurethane or polyurethane urea material according to any one of claims 1 to 7, or the polyurethane or polyurethane urea material prepared by the preparation method according to claim 8, as a raw material for implantable / interventional medical devices.
Citation Information
Patent Citations
Device for stacking bags
GB1550156A
Method for preparing artificial nucleus pulposus prosthetic material
CN101874902A
Organic silicon modified polyurethane elastomer and preparation method thereof
CN115028797A